Jardins secretos e galerias abertas: os fatos, os frutos e as cores do Setor Sul em Goiânia-GO - Mello, Danila Laiana da Silva (2024)
This master's thesis has the main objective of studying the space of Setor Sul, as the firstneighborhood of Goiânia-GO planned for housing, paying attention to its urban design dedicated to gardens and open galleries. A historical study of the gestation/germination of this neighborhood is carried out, as well as its transformations over time, to highlight the change in the function of the spatial configuration. In the researcher's interaction withthe space, the aim is to demonstrate the importance of this neighborhood as a space for sensitive experience both in terms of culture and art, with attention to the cultural centerslocated there, and in terms of the experience made possible by the act of wandering around its squares and forests as secret zones to be discovered by the city's inhabitants. The product of this experience is images in cyanotypes, created by inspiration from the urban nature of Setor Sul, produced by the encounter of facts, fruits and colors of leavesand flowers.